2015
DOI: 10.1016/j.mito.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic targeting of sirtuin and PPAR signaling improves longevity and mitochondrial physiology in respiratory chain complex I mutant Caenorhabditis elegans

Abstract: Mitochondrial respiratory chain (RC) diseases are highly morbid multi-systemic conditions for which few effective therapies exist. Given the essential role of sirtuin and PPAR signaling in mediating both mitochondrial physiology and the cellular response to metabolic stress in RC complex I (CI) disease, we postulated that drugs that alter these signaling pathways either directly (resveratrol for sirtuin, rosiglitazone for PPARγ, fenofibrate for PPARα), or indirectly by increasing NAD+ availability (nicotinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 62 publications
7
62
0
1
Order By: Relevance
“…After filtration, samples were loaded onto a HPLC system, using an YMC-Pack ODS-A column (5 μm, 4.6 × 250 mm) preceded by a guard column. NAD + and NADH peak areas were integrated by the Shimadzu Lab Solution software with standard curves normalized to protein (31).…”
Section: Methodsmentioning
confidence: 99%
“…After filtration, samples were loaded onto a HPLC system, using an YMC-Pack ODS-A column (5 μm, 4.6 × 250 mm) preceded by a guard column. NAD + and NADH peak areas were integrated by the Shimadzu Lab Solution software with standard curves normalized to protein (31).…”
Section: Methodsmentioning
confidence: 99%
“…With this idea, more NAD + /NADH therapies are being created. In a study of gas-1 mutant worms, nicotinic acid (NA) and resveratrol both improved survival of the worms [221]. NA helped decrease the amount of ROS in the worms system and it was suggested that the NA increased NAD + pools which can help maintain Sirt3 acetylation patterns.…”
Section: Mitochondrial Targeted Therapiesmentioning
confidence: 99%
“…20,21 Briefly, worms were treated with either 1 μM flunarizine or 0.1% DMSO buffer control from the early development L1-larval stage. Upon reaching the first day of egg-laying, synchronous populations of young adults were moved to 3.5 cm NGM plates spread with OP50 E. coli , either 1 μM flunarizine or 0.1% DMSO buffer control, and 10 μM MitoTracker Green FM (to evaluate relative mitochondrial mass) for 24 hours.…”
Section: Methodsmentioning
confidence: 99%